A Review Paper on Greenhouse Monitoring System - Pradeep Mali; Prasad Ghorpade; Satendra Yadav; Manish Bhelande (Journal of Electronic Design Engineering, 2021)
As we know internet of things plays a very important part in improving our family lives, hence we can use it to improve our greenhouse systems. By modernizing our greenhouse we can develop our nation into a more progressed country and then it will make us happier about our nation. By using IoT we also support the agriculture system of our nation. It brings more growth to our products and also increases the quality of crops. By utilizing our resources we can minimize our cost of production and make hide profits. Arduino Uno is a device that is usually used for making simple and cheap automated systems. Greenhouse is a structure that is made of walls comprising glass and it has all the required things in it. In daytime or at night it is made in such a way that it grows without any interruption. By using cloud computing we can make the system even bigger and it will start showing its effect on the results and new Inventions will take place. By connecting the system to the internet we move one step further and start to create something great which will empower our people to create such more inventions.: It is the backbone of the bright future in the field of electronics and it will pave a new way for new technologies to come and we will be using them for the betterment of our society.